Addressing Learning Needs on the Use of Metagenomics in Antimicrobial Resistance Surveillance - Duarte, Ana Sofia Ribeiro; Stärk, Katharina D. C.; Munk, Patrick; Leekitcharoenphon, Pimlapas; Bossers, Alex; Luiken, Roosmarijn; Sarrazin, Steven; Lukjancenko, Oksana; Pamp, Sünje Johanna; Bortolaia, Valeria; Nissen, Jakob Nybo; Kirstahler, Philipp; et al. (Frontiers in Public Health, 2020)
One Health surveillance of antimicrobial resistance (AMR) depends on a harmonised method for detection of AMR. Metagenomics-based surveillance offers the possibility to compare resistomes within and between different target populations. Its potential to be embedded into policy in the future calls for a timely and integrated knowledge dissemination strategy. We developed a blended training (e-learning and a workshop) on the use of metagenomics in surveillance of pathogens and AMR. The objectives were to highlight the potential of metagenomics in the context of integrated surveillance, to demonstrate its applicability through hands-on training and to raise awareness to bias factors. The target participants included staff of competent authorities responsible for AMR monitoring and academic staff. The training was organized in modules covering the workflow, requirements, benefits and challenges of surveillance by metagenomics. The training had 41 participants. The face-to-face workshop was essential to understand the expectations of the participants about the transition to metagenomics-based surveillance. After the training, the e-learning component was revised and released as a Massive Open Online Course (MOOC), now available at https://www.coursera.org/learn/metagenomics. This course has run in more than 20 sessions, with more than 3000 learners enrolled, from more than 120 countries. Blended learning and MOOCs are useful tools to deliver knowledge globally and across disciplines. The released MOOC can be a reference knowledge source for the international public health community engaged in the application of metagenomics in surveillance.